Access and time as the main determinants of healthy lifestyle choices, in a sample of Portuguese adults - Pinto, Paula (2022)
Mediterranean diet (MD), regular physical activity (PA), non-smoking, and adequate rest are healthy lifestyle habits that reduce risk of non-communicable diseases. Despite health campaigns and policies enforced by the Portuguese Government, tobacco smoking and overweight, derived from a combination of sedentarism and non-healthy food patterns, have been steadily increasing in the Portuguese adult population. The present study aimed to assess the predisposition to change habits leading to a healthier lifestyle in a convenience sample of 206 Portuguese adults and identify external factors that could help to overcome psychological barriers and prompt these changes.  Most of the participants were predisposed to improve their own and the community well-being through the implementation of healthier lifestyle habits (83.0%). A high percentage of participants reported they would like to improve MD food habits (81.6%), followed by regular PA (65.0 %), sleep 7 to 8 hours per night (47 %), and quit smoking (22.3%). Compared to women, a higher proportion of men reported they should increase fruit consumption (62.5% men, 42.1% women, p=0.02), and whole cereals (30% men, 13.5% women, p=0.017), as well as to reduce red meat (42.5% men, 23.8% women, p=0.02), and reduce butter and increase olive oil consumption (32.5% men, 15.9% women, p=0.022). More access to healthier foods and local producers was reported by most participants (48.5%) as the main external factor that would facilitate the adoption of healthier food choices. More time was the main factor reported to adopt regular PA (62,6%).